Prediction of CO2/O2 absorption selectivity using supported ionic liquid membranes (SILMs) for gas–liquid membrane contactor - Ramli, Nurul Ain; Hashim, Nur Awanis; Aroua, Mohamed Kheireddine (Taylor & Francis, 2018)
Given their unique and tunable properties as solvents, ionic liquids (ILs) have become a favorable solvent option in separation processes, particularly for capturing carbon dioxide (CO2). In this work, a simple method that can be used to screen the suitable IL candidates was implemented in our modified gas–liquid membrane contactor system. Solubilities, selectivities of CO2, nitrogen (N2), and oxygen (O2) gases in imidazolium-based ILs and its activity coefficients in water and monoethanolamine (MEA) were predicted using conductor-like screening model for real solvent (COSMO-RS) method over a wide range of temperature (298.15–348.15 K). Results from the analysis revealed that [emim] [NTf2] IL is a good candidate for further absorption process attributed to its good hydrophobicity and CO2/O2 selectivity characteristics. While their miscibility with pure MEA was somehow higher, utilizing the aqueous phase of MEA would be beneficial in this stage. Data on absorption performances and selectivity of CO2/O2 are scarce especially in gas–liquid membrane contactor system. Therefore, considering [emim] [NTf2] IL as a supporting material in supported ionic liquid membranes (SILMs), using aqueous phase of MEA as an absorbent would result in a great membrane-solvent combination system in furthering our gas–liquid membrane contactor process. In conclusion, COSMO-RS is a potentially great predictive utility to screen ILs for specified separation applications. In addition, this work provides useful results for the [emim] [NTf2]-SILMs to be extensively applied in the field of CO2 capture and selective O2 removal.